2022
DOI: 10.1088/1478-3975/ac70a1
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional acoustic potential landscapes guide the neurite outgrowth and affect the viability of B35 neuroblastoma cells

Abstract: On the way towards neuronal stimulation and signalling, standing surface acoustic waves (SSAW) have become a widely used technique to create well-defined networks of living cells in vitro during the past years. An overall challenge in this research area is to maintain cell viability in long-term treatments long enough to observe changes in cellular functions. To close this gap, we here investigate SSAW-directed neurite outgrowth of B35 (neuroblastoma) cells in microchannels on LiNbO3 chips, employing one-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…As mentioned above, for the here employed pulsed SAW powers the increase in temperature is very low (∆T ⩽ 0.2 K, cf SI figure 1). Previous studies already proved that pulsed SAW signals are a useful tool to reduce temperature effects and maintain cell viability while also maintaining the amplitude of the applied wave for cell culture applications [10]. In the context of wound healing stimulation, Brugger et al showed that SAW treatment of wounds with a continuous P in = 21 dBm signal reduces the proliferation rate and does not induce a stimulation effect compared to moderate SAW powers [13].…”
Section: Mechanic Vibration As Key Driver Of Saw Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, for the here employed pulsed SAW powers the increase in temperature is very low (∆T ⩽ 0.2 K, cf SI figure 1). Previous studies already proved that pulsed SAW signals are a useful tool to reduce temperature effects and maintain cell viability while also maintaining the amplitude of the applied wave for cell culture applications [10]. In the context of wound healing stimulation, Brugger et al showed that SAW treatment of wounds with a continuous P in = 21 dBm signal reduces the proliferation rate and does not induce a stimulation effect compared to moderate SAW powers [13].…”
Section: Mechanic Vibration As Key Driver Of Saw Stimulationmentioning
confidence: 99%
“…The generation of SAW on a chip for the stimulation, manipulation and non-invasive analysis of cells has become an established method in cell biology over the past years [8]. Previous studies show that neurite outgrowth of neuroblastoma cells and of primary neurons can be guided by acoustically modulated standing SAW in microchannels [9,10]. In the field of stimulation, Stamp et al showed that travelling SAW at about f SAW = 160 MHz can accelerate SaOs-2 cell growth in wound healing assays by up to 17% [11].…”
Section: Introductionmentioning
confidence: 99%